Titles of research projects (2000)
The research reports corresponding to the titles we list in the following pages can be consulted in the Foreign Languages Department at Universidad Nacional de Colombia. There, we can find a detailed account of the theoretical issues that led teachers to undertake classroom research. Reference is also made to research procedures and findings in the teaching settings where investigations were carried out.